1999
DOI: 10.1111/j.1572-0241.1999.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility Valuations for Outcome States of Colorectal Cancer

Abstract: We measured utilities for stage-dependent outcome states of CRC in a sample of persons who had previously undergone removal of colorectal adenoma. We found that our participants were able to differentiate between the presented outcome states and assigned lower utility to increasingly morbid states. Our results show that stage-dependent morbidity is an important consideration in CRC and should be incorporated into any decision analysis model evaluating the cost-effectiveness of CRC screening or surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 35 publications
1
127
0
Order By: Relevance
“…Warren et al 64 Gatto et al 13 Levin et al 66 Ness et al 66 Other diseases We used utility scores published by Sullivan and Ghushchyan. 67,68 Sullivan et al 67,68 population of 100,000 individuals aged 50 years old, representative of the U.S. population.…”
mentioning
confidence: 99%
“…Warren et al 64 Gatto et al 13 Levin et al 66 Ness et al 66 Other diseases We used utility scores published by Sullivan and Ghushchyan. 67,68 Sullivan et al 67,68 population of 100,000 individuals aged 50 years old, representative of the U.S. population.…”
mentioning
confidence: 99%
“…The valuations they provided were of similar magnitude as utilities found in earlier research on cancer patients. Ness et al (1999) measured standard gamble scores for outcome states of colorectal cancer in a sample of 81 patients who had previously undergone resection of colorectal carcinoma. They found standard gamble scores of 0.84 for 'own health', 0.74 for the health state 'disease free after resection' and 0.25 for 'metastatic/irresectable'.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer: Based again on the studies of van den Brink et al 12 and Ness et al 13 , utility values for relapse were reported to be in the range 0.24-0.67. We therefore assumed a midpoint value of 0.45 in the base-case analysis for patients with relapsed colon cancer.…”
Section: Utility Associated With Relapsed Stage III Colonmentioning
confidence: 99%
“…Utility Associated with "Disease-free" Stage III Colon Cancer: Based on the studies of van den Brink et al 12 and Ness et al 13 , the utility values for stage iii colon cancer patients diagnosed with the disease or surviving disease-free were in the range 0.63-0.89. A midpoint value of 0.76 was chosen, meaning that each patient entered the model with a utility of 0.76.…”
Section: Quality Of Life and Health Utilitymentioning
confidence: 99%